Differentially expressed genes in the pre-eclamptic placenta: a systematic review and meta-analysis. - C Emily Kleinrouweler; Miranda van Uitert; Perry D Moerland; Carrie Ris-Stalpers; Joris A M van der Post; Gijs B Afink (PLoS ONE)
Objective To systematically review the literature on human gene expression data of placental tissue in pre-eclampsia and to characterize a meta-signature of differentially expressed genes in order to identify novel putative diagnostic markers. Data sources Medline through 11 February 2011 using MeSH terms and keywords related to placenta, gene expression and gene expression arrays; GEO database using the term "placent*"; and reference lists of eligible primary studies, without constraints. Methods From 1068 studies retrieved from the search, we included original publications that had performed gene expression array analyses of placental tissue in the third trimester and that reported on differentially expressed genes in pre-eclampsia versus normotensive controls. Two reviewers independently identified eligible studies, extracted descriptive and gene expression data and assessed study quality. Using a vote-counting method based on a comparative meta-profiling algorithm, we determined a meta-signature that characterizes the significant intersection of differentially expressed genes from the collection of independent gene signatures. Results We identified 33 eligible gene expression array studies of placental tissue in the 3(rd) trimester comprising 30 datasets on mRNA expression and 4 datasets on microRNA expression. The pre-eclamptic placental meta-signature consisted of 40 annotated gene transcripts and 17 microRNAs. At least half of the mRNA transcripts encode a protein that is secreted from the cell and could potentially serve as a biomarker. Conclusions In addition to well-known and validated genes, we identified 14 transcripts not reported previously in relation to pre-eclampsia of which the majority is also expressed in the 1(st) trimester placenta, and three encode a secreted protein.